L = n → ∞ lim ( e 2 n ( e − e n ) ) − n ; e n = ( 1 + n 1 ) n
If L can be expressed as e A / B for positive coprime integers A , B , submit the value of A + B as your answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great problem! But I am not happy with my solution. I am looking for a better one(especially the Laurent series part, I didn't want to take that in, it just came). There must be a better approach. BTW, this problem becomes greater due to such an unexpected answer. Where the hell do you see such an answer? Looking forward for more from you! ⌣ ¨
Log in to reply
You don't need to use Laurent series. Just let f(x) = (1+x)^(1/x), do logarithmic differentiation, then you can find the Maclaurin Series for it. And you will get the answer.
Log in to reply
Oh yeah! That's nicer. Thanks! How did I just miss that!
( e 2 n ( e − e n ) ) − n = ( e 2 n ( e − ( 1 + n ( n 1 ) + 2 n ( n − 1 ) ( n 2 1 ) + 6 n ( n − 1 ) ( n − 2 ) ( n 3 1 ) + . . . ) ) ) − n = ( e 2 n ( e − ( ∑ k = 0 n k ! 1 ) + n 1 ( ∑ k = 0 n 2 ( k ! ) k ( k − 1 ) ) − n 2 1 ( ∑ k = 0 n 2 4 ( k ! ) k ( k − 1 ) ( k − 2 ) ( 3 k − 1 ) ) + O ( n 3 1 ) ) − n = ( e 2 n ( ( ∑ k = n + 1 ∞ k ! 1 ) + n 1 ( ∑ k = 0 n 2 ( k ! ) k ( k − 1 ) ) − n 2 1 ( ∑ k = 0 n 2 4 ( k ! ) k ( k − 1 ) ( k − 2 ) ( 3 k − 1 ) ) + O ( n 3 1 ) ) − n = ( e O ( n ! 1 ) + ( ∑ k = 0 n k ! k ( k − 1 ) ) − n 1 ( ∑ k = 0 n 1 2 ( k ! ) k ( k − 1 ) ( k − 2 ) ( 3 k − 1 ) ) + O ( n 2 1 ) ) − n = ( e ( ∑ k = 0 n k ! 1 ) − n 1 ( ∑ k = 0 n 1 2 ( k ! ) 3 k + 8 ) + O ( n 2 1 ) ) − n = ( e ( ∑ k = 0 n k ! 1 ) − n 1 ( ∑ k = 0 n 4 ( k ! ) 1 + ∑ k = 0 n 3 ( k ! ) 2 ) + O ( n 2 1 ) ) − n = ( e e − ( ∑ k = n + 1 ∞ k ! 1 ) − n 1 ( ∑ k = 0 n 4 ( k ! ) 1 + ∑ k = 0 n 3 ( k ! ) 2 ) + O ( n 2 1 ) ) − n = ( e e − O ( ( n + 1 ) ! 1 ) − 1 2 1 1 n 1 ∑ k = 0 n k ! 1 + O ( n 2 1 ) ) − n = ( e e − 1 2 1 1 n 1 ( e − ∑ k = n + 1 ∞ k ! 1 ) + O ( n 2 1 ) ) − n = ( e e − 1 2 1 1 n 1 ( e ) − O ( ( n + 2 ) ! 1 ) + O ( n 2 1 ) ) − n = ( 1 − 1 2 1 1 n 1 + O ( n 2 1 ) ) − n ................................................................................................................................................. lim n → ∞ ( 1 − 1 2 1 1 n 1 + O ( n 2 1 ) ) − n = exp ( lim n → ∞ − n ln ( 1 − 1 2 1 1 n 1 + O ( n 2 1 ) ) ) = exp ( lim n → ∞ n − 1 ln ( 1 − 1 2 1 1 n 1 + O ( n 2 1 ) ) ) = exp ( lim n → ∞ n 2 1 1 − 1 2 1 1 n 1 + O ( n 2 1 ) 1 ( 1 2 1 1 n 2 1 + O ( n 3 1 ) ) ) = exp ( lim n → ∞ 1 − 1 2 1 1 n 1 + O ( n 2 1 ) 1 ( 1 2 1 1 + O ( n 1 ) ) ) = e 1 1 / 1 2
And for those who may be picky about differentiating the factorial functions (which goes unseen), replace them with the gamma function. (Hm, a sidenote: I wonder what other types of interpolations of n ! exist besides the gamma function.)
Problem Loading...
Note Loading...
Set Loading...
ln ( L ) = n → ∞ lim ln ( ( e 2 n ( e − ( 1 + n 1 ) n ) ) − n )
= n → ∞ lim − n ln ( 2 n − e 2 n ( 1 + n 1 ) n )
= n → ∞ lim − n ln ( 1 − ( 1 − 2 n + e 2 n ( 1 + n 1 ) n ) )
= n → ∞ lim n k = 1 ∑ ∞ k ( 1 − 2 n + e 2 n ( 1 + n 1 ) n ) k
= n → ∞ lim n ( 1 − 2 n + e 2 n ( 1 + n 1 ) n ) + 2 n ( 1 − 2 n + e 2 n ( 1 + n 1 ) n ) 2 + ⋯
We will consider the Laurent series for e ( 1 + n 1 ) n = 1 − 2 n 1 + 2 4 n 2 1 1 − 1 6 n 3 7 + O ( n 4 1 )
We will only consider the first term of our original series and use the value of Laurent series(to a few terms as after a few, denominator will have n and that's unimportant),
n − 2 n 2 + 2 n 2 ( 1 − 2 n 1 + 2 4 n 2 1 1 ) = 1 2 1 1
ln ( L ) = 1 2 1 1
L = e 1 1 / 1 2